GERAKAN HIJRAH DAN KONSTRUKSI EMOSI KEISLAMAN DI PERKOTAAN - Sahlul Fuad (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. This paper discusses the construction of Islamic Islamic emotions in urban areas as a reflection of the influence of the hijrah movement that is widespread in Indonesia,. The growth of the Muslim middle class and the rapid advancement of information technology in Indonesia has become fertile ground for the increasing migration movement among millennial. The movement of hijrah is an expression of new Islamic emotions that brings together the spirit of religiosity and the lifestyle of the middle class. However, along with the increasing trend of transnational ideologies that lead to fundamentalism and radicalism movements, the migration movement has the potential to support transnational ideological movements targeting young people who are new to Islam. Abstrak. Paper ini membahas tentang konstruksi emosi keislaman muslim perkotaan sebagai refleksi atas pengaruh gerakan hijrah yang berkembang luas di Indonesia, khususnya di kawasan perkotaan. Pertumbuhan kelas menengah muslim dan kemajuan teknologi informasi yang pesat di Indonesia menjadi lahan yang subur bagi meningkatnya gerakan hijrah di kalangan millenial. Gerakan hijrah merupakan ekspresi emosi keislaman baru yang mempertemukan antara semangat religiusitas dan gaya hidup kelas menengah. Namun, seiring dengan meningkatnya kecenderungan ideologi transnasional yang mengarah pada gerakan fundamentalisme dan radikalisme, gerakan hijrah menjadi potensial sebagai pendukung gerakan ideologi transnasional yang menyasar para generasi muda yang baru mengenal Islam.